A Ratiometric Fluorescent Probe for Cisplatin: Investigating the Intracellular Reduction of Platinum(IV) Prodrug Complexes. (4th December 2018) - Ong, Jun Xiang; Lim, Carine Shu Qing; Le, Hai Van; Ang, Wee Han
Abstract: The Pt IV prodrug strategy has emerged as an excellent alternative to tackle the problems associated with conventional Pt II drug therapy. However, there is a lack of tools to study how this new class of Pt IV drugs are processed at the cellular level. Herein, we report the first ratiometric probe for cisplatin detection and use it to investigate Pt IV anticancer complexes in biological systems. The probe was able to distinguish between cisplatin and its Pt IV derivatives, allowing us to probe the intracellular reduction of Pt IV prodrug complexes. The correlation between the amount of active Pt II species available after intracellular reduction of Pt IV complexes and their cytotoxicity and the role glutathione plays in the reduction of Pt IV complexes were investigated.